THE EFFECT OF DIABETES FAMILY EMPOWERMENT ON DIET COMPLIANCE IN ELDERLY PEOPLE WITH TYPE 2 DIABETES MELLITUS - A. Ali, Risaldi; Nabil Asshiddiqi, M. Ischaq; Yuliawan, Deny; Indrayana, Sofyan (Jurnal Keperawatan Sriwijaya, 2026)
Aim: This study aimed to determine the effect of empowering diabetes-sensitive families on dietary adherence among patients with type 2 diabetes in the Sedayu 2 Community Health Center (Puskesmas) area in Bantul. Method: A pre-experimental, one-group pre-test, post-test design was used. A sample of 35 respondents was selected using a purposive sampling technique. The research instruments were the Perceived Dietary Adherence Questionnaire (PDAQ) and a pre-tested booklet. This study used the Shapiro-Wilk normality test, and data analysis used bivariate paired t-tests. Results: The pre-test results showed that 29 respondents (82.9%) were compliant with the diet, while 6 respondents (17.1%) were non-compliant. The post-test results showed that 35 respondents (100%) were compliant with the diet. The paired t-test showed a p-value of 0.000 (<0.05), indicating a significant difference between dietary adherence before and after the intervention. Conclusion: Empowering diabetes-sensitive families has an impact on dietary compliance in patients with type 2 diabetes mellitus in the Sedayu 2 Bantul Community Health Center work area.